Factors influencing students' performance at Universiti Teknologi MARA (UiTM) Kelantan branch / Mas Ayu Diana Mohd Fauzi ...[et al.] - Mohd Fauzi, Mas Ayu Diana; Hassan, Zaleha; Setapa, Mariam; Ramlee, Nur Atiqah Zakiyyah; Ab Rahman, Siti Maziah (Universiti Teknologi MARA Cawangan Kelantan, 2020)
In thenew Era of fourth Industrial Revolution (IR 4.0), high qualityof education is crucial in as much as it can benefit students when they embark on career paths. Thus, academic performance is an important measurement for employersto choose their future employees. Ones who are academically successfulwill have better chances to earn higher salaries and less dependent on social assistance. Studentperformancemeasurementhasreceivedconsiderableattentioninpreviousresearch,itisoneofthechallengingaspectsofacademicliterature,andstudentperformanceisinfluencedbyfriends,self-motivationandfamilyfactors.In the light of this issue, this research is carried outto discover the performance of the diploma students in the Faculty of Business and Management, Universiti Teknologi MARA KelantanBranch (UiTMCK), Malaysia. Furthermore, this study is to determine the relationship between factorsinfluencing students’ performance and their resultsin UiTMCK. Data were collected from 35 students of Diploma inBusiness Studies through a question survey. The data were analyses using SmartPLS 3.2.1 software. The analysis shows both self-motivation and family have strong direct relationships with the students’ performance butfriendswerenot significantly related to students’ performance. Thus, the hypothesis 2 and 3 was accepted